The effect of π–π stacking interaction of the indole ring with the coordinated phenoxyl radical in a nickel(ii)-salen type complex. Comparison with the corresponding Cu(ii) complex. Issue 32 (28th June 2019) - Oshita, Hiromi; Suzuki, Takashi; Kawashima, Kyohei; Abe, Hitoshi; Tani, Fumito; Mori, Seiji; Yajima, Tatsuo; Shimazaki, Yuichi
Abstract : A side-chain indole ring showed stacking interaction with the Ni(ii )-phenoxyl radical, but had smaller effects in comparison with that of the Cu(ii )-phenoxyl radical. Abstract : In order to gain new insights into the effect of the π–π stacking interaction of the indole ring with the phenoxyl radical moiety as seen in the active form of galactose oxidase, we have prepared Ni(ii ) complexes of a methoxy substituted salen-type ligand containing a pendent indole ring on the dinitrogen chelate backbone and characterized their one-electron oxidized forms. The X-ray crystal structure analysis and the other physicochemical experiments of the Ni(ii ) complex revealed no significant intramolecular interaction of the indole ring with the coordination plane. On the other hand, the X-ray crystal structures of the oxidized Ni(ii ) complex exhibited the π–π stacking interaction of the indole ring mainly with one of the two phenolate moieties. While the phenoxyl radical electron was delocalized on the two phenolate moieties in the Ni(ii )-salen coordination plane, the phenolate moiety in close contact with the indole moiety was considered to be the initial oxidation locus, indicating that the indole ring interacted with the phenoxyl radical by π–π stacking. The UV–vis–NIR spectrum of the oxidized Ni(ii ) complex with the pendent indole ring was different from that of the complex without the side chain indole ring, but the differences were rather small in comparison with the oxidized Cu(ii )-salen complexes with the π–π stacking interaction of the indole ring. Such differences are due to the electronic structure difference, the localized radical electron on one of the phenolate moieties in the oxidized Cu(ii ) complexes being more favorable for the π–π stacking interaction.